2007
DOI: 10.1063/1.2764217
|View full text |Cite
|
Sign up to set email alerts
|

High permittivity in Zr doped NiO ceramics

Abstract: We report on measurements of the dielectric permittivity of NiO-based ceramics doped with Zr ͑ZNO͒. Samples were prepared by the traditional solid-state reaction method. The concentration of Zr has an effect on the dielectric properties of ZNO ceramics. High permittivity values ͑ϳ10 4 ͒ were observed which remain almost constant from 200 K to 350 K at low frequencies. The high-dielectric-constant response of the ZNO ceramics is attributed mainly to a grain boundary ͑internal͒ barrier layer capacitance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…An exceptionally high value of about 10 4 is found for all compositions together with a strong frequency dependence at the lower frequency region. Low frequency dielectric constants are quite large compared with 30 of pure nickel oxide [19]. Threshold frequency corresponding to a sharp rise in 1 moves towards lower frequency region and 1 decreases with increase of Al content.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…An exceptionally high value of about 10 4 is found for all compositions together with a strong frequency dependence at the lower frequency region. Low frequency dielectric constants are quite large compared with 30 of pure nickel oxide [19]. Threshold frequency corresponding to a sharp rise in 1 moves towards lower frequency region and 1 decreases with increase of Al content.…”
Section: Resultsmentioning
confidence: 85%
“…It is found that Ti and K co-doped NiO also show remarkable dielectric properties [17,18]. Replacement of Ni by tetravalent Zr gives rise to a high dielectric constant [19]. The incorporation of Li doped NiO in polyvinylidene fluoride polymer yields a high dielectric constant and low electrical conductivity near the percolation threshold [20].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different element doped NiO, (Li, Fe) and (Li, V) doped NiO have shown to exhibit giant dielectric response [1,2]. The observation of high dielectric constant in doped NiO is attributed mainly to a grain boundary barrier layer capacitance [9,47,48], which can arise due to the formation of core/shell structure with conductive grain as core and resistive boundary as shell [1,2].…”
Section: Evolution Of Electrical Properties Of Nio With Transition Mementioning
confidence: 99%
“…The relaxation time τ has the relationship with temperature and activation energy, expressed as the following 25 τ τ…”
mentioning
confidence: 99%
“…The relaxation time τ has the relationship with temperature and activation energy, expressed as the following where τ 0 is the relaxation time at infinite temperature, U the activation energy for relaxation, T the absolute temperature, and k the Boltzmann constant.…”
mentioning
confidence: 99%